Comparative Noise Analysis of Readout Circuit in Hemispherical Resonator Gyroscope - Zhihao Yu; Libin Zeng; Changda Xing; Lituo Shang; Xiuyue Yan; Jingyu Li (Micromachines)
In high-precision Hemispherical Resonator Gyroscope (HRG) control systems, readout circuit noise critically determines resonator displacement detection precision. Addressing noise issues, this paper compares the noise characteristics and contribution mechanisms of the Transimpedance Amplifier (TIA) and Charge-Sensitive Amplifier (CSA). By establishing a noise model and analyzing circuit bandwidth, the dominant role of feedback resistor thermal noise in the TIA is revealed. These analyses further demonstrate the significant suppression of high-frequency noise by the CSA capacitive feedback network. Simulation and experimental results demonstrate that the measured noise of the TIA and CSA is consistent with the theoretical model. The TIA output noise is 25.8 <semantics>μVrms</semantics>, with feedback resistor thermal noise accounting for 99.8%, while CSA output noise is reduced to 13.2 <semantics>μVrms</semantics>, a reduction of 48.8%. Near resonant frequency, the equivalent displacement noise of the CSA is <semantics>1.69×10−14<mspace width="0.222222em"></mspace>m/<msqrt>Hz</msqrt></semantics>, a reduction of 86.7% compared to the TIA’s <semantics>1.27×10−13<mspace width="0.222222em"></mspace>m/<msqrt>Hz</msqrt></semantics>, indicating the CSA is more suitable for high-precision applications. This research provides theoretical guidance and technical references for the topological selection and parameter design of HRG readout circuits.